2009
DOI: 10.1177/1744987108096972
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two tools developed to assess the needs of older people with complex care needs

Abstract: Greater standardisation of assessments of older people with complex care needs is a requirement of UK policy. This study explores the practicability and validity of two assessment tools, Minimum Data Set Resident Assessment Instrument (MDS-RAI) and EASY-Care. Participants, aged 65 years or over, living in care homes or awaiting hospital discharge, were assessed using randomly allocated paired instruments. Client evaluation questionnaires on the practicability of the tools were completed. Short Form 12 (SF12) q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…), a consensus was reached of nine papers which were assessed to be of acceptable quality, summarised in Table 2 . Three papers (from one study) included the use of EASY-Care administered in hospital with patients no longer receiving consultant-led care [ 9 – 11 ]. The sample was predominantly from community-dwelling older people, so they were included in the review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…), a consensus was reached of nine papers which were assessed to be of acceptable quality, summarised in Table 2 . Three papers (from one study) included the use of EASY-Care administered in hospital with patients no longer receiving consultant-led care [ 9 – 11 ]. The sample was predominantly from community-dwelling older people, so they were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…Due to limited evidence outside of a research context, we are unable to say whether EASY-Care is useful in practice or not. However, there is evidence that it is preferred over other accredited tools [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However it appeared that no valid and reliable instrument had been designed and developed for nurses specifically to facilitate the assessment of psychological status in patients with SCI. In the current study we aimed to develop such an instrument on the basis of literature relating to the development of assessment instruments within health care settings, [16][17][18] a contemporary understanding of emotion, 19,20 and in accordance with established methods of scale development. 21 Plutchik's emotion theory, 19 which argues that eight primary emotions are of crucial relevance to adaptation in response to illness, strengthened the focus of our interviews on identifying core emotional and psychological states present in the patients.…”
Section: Introductionmentioning
confidence: 99%
“…The study also used statistical methods to analyse the assessment data collected and to assess the construct and criterion validity of the tools. The results of the full study are reported in Lambert et al (2005).…”
Section: Introductionmentioning
confidence: 99%